Mesoscopy and scanning electron microscopy of the trabecular projections in the superior sagittal sinus - Petroni, S.; Tamega, O. J.; Tirapelli, L. F.; Soares, J. C. (Karger, 2003)
The trabecular projections of the human superior sagittal sinus were classified into types and subtypes according to spatial arrangement and shape. The horizontal and vertical projections direct laminar blood flow, while the conic type, which is avalvular, protects the openings of the superior cerebral veins in the superior sagittal sinus. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: dura mater; sagittal sinus, superior; trabecular projections